COMING OUT AND COMING UP: QUANTIFYING QUEER IMMATERIAL LABOR - Homant, Ellie; Russell, Aspen (AoIR Selected Papers of Internet Research, 2023)
Like the broader beauty industry, YouTube’s beauty vlogosphere has historically been dominated by gender- and sexually normative White woman. However, in recent years, a new class of racially diverse, queer-identified beauty vloggers have risen to fame on the platform, garnering millions of subscribers and lucrative brand deals. Previous scholarship has identified the specific type of labor that queer online content creators undertake as “queer immaterial labor,” which recognizes that (1) immaterial labor is not performed in the same way by creators in online spaces, but rather is structured by complex interplay between a variety of social identities; and (2) that queer influencers undertake labor that is specific to the queer community (e.g. performance of the coming-out narrative, employing queer cultural resources) (Homant and Sender, 2019). Our goal is to use a computational approach to measure its two primary facets: amount of labor and unique labor practices. This can be accomplished by returning to YouTube and expanding the sample of queer and non-queer beauty vloggers with broader metrics for comparison. We will use a mixture of comments, transcripts, and video metadata to characterize and contextualize the amount and type of labor performed by a sample of popular queer beauty vloggers (>100,000 subscribers) in comparison to their straight peers. Our goal is to provide a series of descriptive comparisons across this large sample of beauty vloggers on YouTube. Insights will allow us to directly point to areas of potentially inequitable output and differences in labor practices across these two groups.